ANALISIS POLA PEMBERDAYAAN PETERNAK MISKIN DI KAMPOENG TERNAK NUSANTARA DOMPET DHUAFA - Efri Syamsul Bahri; Sholihat Sholihat (Universitas Muhammadiyah Sidoarjo, 2016)
The activity of livestock village Nusantara “Kampung Ternak Nusantara” is focused on the empowerment to the poor cattleman by utilizing zakat funds. This research is aimed to determine the empowerment pattern of the poor cattlemanas well as the supporting and obstacle factors. It is a descriptive qualitative research. The data are collected by doing interviews, observations and documentations. The results show that the pattern empowerment to the poor cattleman, are dividedinto 3 stages. They are 1) the empoweringgoal setting,2) the process implementation of the empowerment 3) the resultsimplementation of empowerment. The empowerment supporting factors include; society environment, hard work and the cattleman effort. While, the obstacle factors include: the difficultyfeedingto the livestock whenthe dry season, knowledge and the skill of the cattleman who have not been optimized yet